A chromosome-scale and haplotype-resolved genome assembly of carnation (Dianthus caryophyllus) based on high-fidelity sequencing - Jiang, Heling; Zhang, Xiaoni; Leng, Luhong; Gong, Desheng; Zhang, Xiaohui; Liu, Junyang; Peng, Dan; Wu, Zhiqiang; Yang, Yingxue (Frontiers in Plant Science, 2023)
Dianthus caryophyllus is an economic species often considered excellent cut flowers and is suitable for bouquets and gardens. Here, we assembled the haplotype-resolved genome of D. caryophyllus ‘Aili’ at the chromosome level for the first time. The total lengths of the two assembled haplotypes of carnation were 584.88 Mb for haplotype genome 1 (hap1) and 578.78 Mb for haplotype genome 2 (hap2), respectively. We predicted a total of 44,098 and 42,425 protein-coding genes, respectively. The remarkable structure variation was identified between two haplotypes. Moreover, we identified 403.80 Mb of transposable elements (TEs) in hap1, which accounted for 69.34% of the genome. In contrast, hap2 had 402.70 Mb of TEs, representing 69.61% of the genome. Long terminal repeats were the predominant transposable elements. Phylogenetic analysis showed that the species differentiation time between carnation and gypsophila was estimated to be ~54.43 MYA. The unique gene families of carnation genomes were identified in ‘Aili’ and previously published ‘Francesco’ and ‘Scarlet Queen’. The assembled and annotated haplotype-resolved D. caryophyllus genome not only promises to facilitate molecular biology studies but also contributes to genome-level evolutionary studies.